2018
DOI: 10.1038/s41467-018-07554-7
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane but not soluble helices fold inside the ribosome tunnel

Abstract: Integral membrane proteins are assembled into the ER membrane via a continuous ribosome-translocon channel. The hydrophobicity and thickness of the core of the membrane bilayer leads to the expectation that transmembrane (TM) segments minimize the cost of harbouring polar polypeptide backbones by adopting a regular pattern of hydrogen bonds to form α-helices before integration. Co-translational folding of nascent chains into an α-helical conformation in the ribosomal tunnel has been demonstrated previously, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 59 publications
2
42
0
Order By: Relevance
“…However, not every polypeptide chain that ultimately adopts helical conformation starts folding inside the peptide exit tunnel. The overall hydrophobicity, propensity to form an α-helix, and the element length are the major determinants of α-helix formation within the tunnel [63]. Indeed, accessibility assays, FRET, and molecular dynamics simulations provide evidence that transmembrane helices favor early compaction during translation to a much larger extent than their soluble counterparts [40,63,64].…”
Section: Folding Inside the Exit Tunnelmentioning
confidence: 99%
“…However, not every polypeptide chain that ultimately adopts helical conformation starts folding inside the peptide exit tunnel. The overall hydrophobicity, propensity to form an α-helix, and the element length are the major determinants of α-helix formation within the tunnel [63]. Indeed, accessibility assays, FRET, and molecular dynamics simulations provide evidence that transmembrane helices favor early compaction during translation to a much larger extent than their soluble counterparts [40,63,64].…”
Section: Folding Inside the Exit Tunnelmentioning
confidence: 99%
“…In the case of transmembrane helical proteins, this effect has led to the proposal of a "twostage model" [9,10], in which the individual helices are first inserted into the membrane, before assembling to their native structure. In the cell, the analogous insertion process is usually accomplished by the translocon machinery [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, experiments investigating helix formation inside the ribosome tunnel demonstrated that hydrophobic transmembrane protein sequences form compacted structures inside the tunnel, suggesting the formation of an α -helix. 11…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the helicity does not increase upon substitution of serine with alanine for D ≥ 14.9 Å However, each VSV-G protein sequence formed a helix within the center of the sequence and this is consistent with prior studies. 11…”
Section: Resultsmentioning
confidence: 99%